Analysis on the performances of a micro gas turbine cogeneration system in sewage treatment plants - Muhammad Zaid, Nor Azlan (2013)
The main role of this study is to analyse the economics performances of micro gas turbine co-generation systems (MGT-CGSs) in order to define the most interesting solutions from economic point of view. The study consist two type of economic analysis, simple and advanced economic analysis. The simple economic analysis is analysis based on the present and previous data collected that no estimation needed. The advanced economic analysis is the analysis that need to consider the estimation for the future value or parameter. The advanced economic analysis give better over view of the economic analysis of the system. Considering operation of the MGT-CGS under various loads and efficiency of the MGT-CGSs under partial road condition, the optimal combination of MGT-CGS (MGT-combination) with different sizes, 30 kW, 65 kW and 200 kW. Economic performance of MGT-CGSs under three typical ambient temperature conditions and three different scale sewage treatment plant was also investigated. It was found that MGT combination has the highest total capital cost for every scale and every temperature condition. Futhermore MGT combination has the highest total electricity sold. Excluding MGT combination total electricity sold higher when the MGT power output higher.